Effect of androgen deprivation therapy on the expression of prostate cancer biomarkers MSMB and MSMB-binding protein CRISP3. - Dahlman, A; Edsjö, A; Halldén, C; Persson, J; Fine, S; Lilja, H; Gerald, W; Bjartell, A (2010)
We have investigated the effects of short-term neoadjuvant and long-term androgen deprivation therapies (ADTs) on β-microseminoprotein (MSMB) and cysteine-rich secretory protein-3 (CRISP3) expression in prostate cancer patients. We also studied if MSMB expression was related to genotype and epigenetic silencing. Using an Affymetrix cDNA microarray analysis, we investigated the expression of MSMB, CRISP3, androgen receptor (AR), KLK3 and Enhancer of Zeste Homologue-2 (EZH2) in tissue from prostate cancer patients receiving (n=17) or not receiving (n=23) ADT before radical prostatectomy. MSMB, CRISP3 and AR were studied in tissue from the same patients undergoing TURP before and during ADT (n=16). MSMB genotyping of these patients was performed by TaqMan PCR. MSMB and KLK3 expression levels decreased during ADT. Expression levels of AR and CRISP3 were not affected by short-term ADT but were high in castration-resistant prostate cancer (CRPC) and metastases. Levels of EZH2 were also high in metastases, where MSMB was low. Genotyping of the MSMB rs10993994 polymorphism showed that the TT genotype conveys poor MSMB expression. MSMB expression is influenced by androgens, but also by genotype and epigenetic silencing. AR and CRISP3 expression are not influenced by short-term ADT, and high levels were found in CRPC and metastases.